Developing Standard Operating Procedure for Production in North Sumatra Construction Companies - Arumbasari, Atita; Rhamadani, Poetri; Christine Sembiring, Anita; Budiman, Irwan (Journal Knowledge Industrial Engineering (JKIE), 2021)
In the industrial era 4.0, the competition between corporate companies is getting tighter. This is a reference for the company's productivity in operating a product or service, one of which is PT.X. It can be seen from the running performance process, PT. X has constraints on the production performance process. Therefore, PT.X seeks to increase productivity in the production process. So that in this study, a proposal design was carried out on a standard operating procedure (SOP) using the Business Process Model (BPM) method. The result of the proposed design with BPM is to minimize the production time by 2 hours 40 minutes so that the production process can run more effectively and efficiently. With that, the best solution in handling this case research provides suggestions on the work process that is running with efficient improvements.